Дефініція поняття "економічна безпека підприємства": основні підходи та особливості - Коптєва (Фадєєва), Ганна Миколаївна (My University, 2019)
У статті проведено контент-аналіз і систематизацію наукових поглядів щодо сутності поняття "економічна безпека підприємства", а також розвиток понятійного апарату теорії менеджменту за рахунок дефініції економічної безпеки як об’єкта управління. На основі систематизації наукових поглядів на сутність поняття "економічна безпека підприємства" узагальнено різні підходи щодо цієї дефініції, а саме "економічна безпека підприємства" розглядається: як стан ефективного використання (ресурсів, потенціалу, діяльності); як стан захищеності (потенціалу підприємства, діяльності підприємства, інтересів тощо); як комплекс (економічних відносин, заходів, властивостей тощо); як характеристика (діяльності, досягнутих та очікуваних результатів діяльності тощо); як розвиток (збалансований і безупинний) тощо. Запропоноване авторське уточнене визначення терміна "економічна безпека підприємства" як комплексної характеристики стану захищеності економічних інтересів підприємства та їхньої узгодженості з наявним потенціалом і заявленими цілями, що дає змогу протистояти різним негативним факторам у процесі економічної діяльності.

Ensuring sustainable development of an enterprise is impossible without an effective system of its economic security based on a developed and implemented development strategy. Under the conditions of socio-economic and political instability, dynamic external environment and unstable development of the national economy, domestic enterprises face many threats to their functioning. Therefore, business entities have to ensure the stability of operations by avoiding or eliminating threats and risks, as well as the efficiency of operations through sound management of resources and business processes. In this regard, the issue of further developing the conceptual apparatus becomes more relevant, which will make it possible to form appropriate economic security management systems at the enterprise. The purpose of the study is content analysis and systematization of scientific views on the essence of the concept of “economic security of the enterprise”, as well as the development of the conceptual apparatus of management theory through the definition of economic security as a management object which will reflect the author’s interpretation of this category and open prospects for further research. On the basis of content analysis and systematization of scientific views regarding the essence of the concept of “economic security of the enterprise” different approaches to this definition were generalized, namely “economic security of the enterprise” is considered: as a state of efficient use (resources, potential, activity); as a state of security (enterprise potential, enterprise activity, interests, etc.); as a complex (economic relations, activities, properties, etc.); as a characteristic (activities, achieved and expected results of activities, etc.); as development (balanced and continuous) and the like. Treating sustainability as a long-term equilibrium between the existing and prospective potential of the enterprise and the goals of its development, we consider it advisable to introduce a characteristic of their consistency, deviation from which causes fluctuations in equilibrium. Thus, it is appropriate to use an integrated approach, according to which the economic security of the enterprise is considered as a complex characteristic of the state of protection of the economic interests of the enterprise and their consistency with the existing potential and stated goals, which makes it possible to counter various negative factors in the process of economic activity. Thus, consideration of the economic security of the enterprise from the point of view of cost-oriented management makes it possible to determine the objects of security management at the enterprise, and the structuring of business processes, resources, factors is the basis for the formation of a fundamentally new concept of “economic security of the enterprise”.
Definition of the concept "economic security of the enterprise": main approaches and features
Keywords: економічна безпека підприємства; ефективність використання ресурсів; захищеність економічних інтересів; потенціал підприємства; загрози; ризики; управління ресурсами; бізнес-процеси; economic security; resource efficiency; protection of economic interests; enterprise potential; threats; risks; resource management; business process